Colossal photo-conductive gain in low temperature processed TiO2 films and their application in quantum dot solar cells - Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K. (Applied Physics Letters, 2017)
Colloidal quantum dot (QD) solar cells have seen remarkable progress in recent past to reach the certified efficiency of 10.6%. Anatase titanium oxide (TiO2) is a widely studied n-type widow layer for the collection of photogenerated electrons in QD solar cells. Requirement of high temperature (similar to 500 degrees C) processing steps proved to be disadvantageous for its applications in flexible solar cells and roll to roll processing, and it also has adverse commercial implications. Here, we report that solar light exposure to low temperature processed (80 degrees C-150 degrees C) TiO2 and niobium doped TiO2 films leads to unprecedented enhancement in their electron densities and electron mobilities, which enables them to be used as efficient n-type layers in quantum dot solar cells. Such photoinduced high conducting states in these films show gradual decay over hours after the light bias is taken off and can be retrieved under solar illumination. On the contrary, TiO2 films processed at 500 degrees C show marginal photo induced enhancements in their characteristics. In bilayer configuration with PbS QDs, photovoltaic devices based on low temperature processed TiO2 films show improved performance over high temperature processed TiO2 films. The stability of photovoltaic devices also improved in low temperature processed TiO2 films under ambient working conditions. Published by AIP Publishing.

Generic and scalable method for the preparation of monodispersed metal sulfide nanocrystals with tunable optical properties - Bera, Abhijit; Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K.; Bhagavatula L. V. Prasad (Langmuir, 2018)
A rational synthetic method that produces monodisperse and air-stable metal sulfide colloidal quantum dots (CQDs) in organic nonpolar solvents using octyl dithiocarbamic acid (C(8)DTCA) as a sulfur source, is reported. The fast decomposition of metal-C(8)DTCA complexes in presence of primary amines is exploited to achieve this purpose. This novel technique is generic and can be applied to prepare diverse CQDs, like CdS, MnS, ZnS, SnS, and In2S3, including more useful and in-demand PbS CQDs and plasmonic nanocrystals of Cu2S. Based on several control reactions, it is postulated that the reaction involves the in situ formation of a metal-C(8)DTCA complex, which then reacts in situ with oleylamine at slightly elevated temperature to decompose into metal sulfide CQDs at a controlled rate, leading to the formation of the materials with good optical characteristics. Controlled sulfur precursor's reactivity and stoichiometric reaction between C(8)DTCA and metal salts affords high conversion yield and large-scale production of monodisperse CQDs. Tunable and desired crystal size could be achieved by controlling the precursor reactivity by changing the reaction temperature and reagent ratios. Finally, the photovoltaic devices fabricated from PbS CQDs displayed a power conversion efficiency of 4.64% that is comparable with the reported values of devices prepared with PbS CQDs synthesized by the standard methods.

Role of surface ligands in determining the electronic properties of quantum dot solids and their impact on photovoltaic figure of merits - Goswami, Prasenjit N.; Mandal, Debranjan; Rath, Arup K. (Nanoscale, 2018)
Surface chemistry plays a crucial role in determining the electronic properties of quantum dot solids and may well be the key to mitigate loss processes involved in quantum dot solar cells. Surface ligands help to maintain the shape and size of the individual dots in solid films, to preserve the clean energy band gap of the individual particles and to control charge carrier conduction across solid films, in turn regulating their performance in photovoltaic applications. In this report, we show that the changes in size, shape and functional groups of small chain organic ligands enable us to modulate mobility, dielectric constant and carrier doping density of lead sulfide quantum dot solids. Furthermore, we correlate these results with performance, stability and recombination processes in the respective photovoltaic devices. Our results highlight the critical role of surface chemistry in the electronic properties of quantum dots. The role of the size, functionality and the surface coverage of the ligands in determining charge transport properties and the stability of quantum dot solids have been discussed. Our findings, when applied in designing new ligands with higher mobility and improved passivation of quantum dot solids, can have important implications for the development of high-performance quantum dot solar cells.

Thiol and halometallate, mutually passivated quantum dot ink for photovoltaic application - Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2019)
Tunable-band-gap colloidal QDs are a potential building block to harvest the wide-energy solar spectrum. The solution-phase surface passivation with lead halide-based halometallate ligands has remarkably simplified the processing of quantum dots (QDs) and enabled the proficient use of materials for the development of solar cells. It is, however, shown that the hallometalate ligand passivated QD ink allows the formation of thick crystalline shell layer, which limits the carrier transport of the QD solids. Organic thiols have long been used to develop QD solar cells using the solid-state ligand exchange approach. However, their use is limited in solution-phase passivation due to poor dispersity of thiol-treated QDs in common solvents. In this report, a joint passivation strategy using thiol and halometallate ligand is developed to prepare the QD ink. The mutually passivated QDs show a 50% reduction in shell thickness, reduced trap density, and improved monodispersity in their solid films. These improvements lead to a 4 times increase in carrier mobility and doubling of the diffusion length, which enable the carrier extraction from a much thicker absorbing layer. The photovoltaic devices show a high efficiency of 10.3% and reduced hysteresis effect. The improvement in surface passivation leads to reduced oxygen doping and improved ambient stability of the solar cells.
Keywords: ligand; mobility; quantum dot; solar cell; surface passivation